Structure dependent active sites of NixSy as electrocatalysts for hydrogen evolution reaction - Chung, Dong Young; Han, Joung Woo; Lim, Dong-Hee; Jo, Jun-Ho; Yoo, Sung Jong; Lee, Hyunjoo; Sung, Yung-Eun (ROYAL SOC CHEMISTRY, 2015)
Structure effects of NiS and Ni3S2 nanoparticles were investigated for their electrocatalytic activity in the hydrogen evolution reaction in both acid and alkaline media. Owing to the different atomic configurations and crystalline structures, there is a hydrogen adsorption energy difference, which induces a difference in the activity. From density functional theory calculations and experimental observations, the importance of designing an electrocatalyst with an appropriate atomic configuration is evident.
Keywords: INITIO MOLECULAR-DYNAMICS; TOTAL-ENERGY CALCULATIONS; AUGMENTED-WAVE METHOD; MOS2 NANOPARTICLES; EDGE SITES; BASIS-SET; OXIDATION; CATALYSTS; KINETICS; METALS